2004
DOI: 10.1093/hsw/29.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Practice with People with Severe Mental Illness: Rewards, Challenges, Burdens

Abstract: The authors surveyed a random sample of 1,200 NASW members in post-master's practice in mental health to identify their attitudes toward practice with people with severe mental illness. Contrary to the literature that claims social workers have abandoned vulnerable populations or have negative attitudes toward this population, the authors found that the majority practice with this clientele and find their practice rewarding. Most of the respondents' frustration and obstacles in practice were related to systemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 0 publications
0
21
1
2
Order By: Relevance
“…Furthermore, this lack of influence could not be attributed to an over-representation of private practitioners in our sample. These findings are somewhat surprising given that previous research, including our earlier descriptive analyses (Newhill & Korr, 2004), indicated that modern-day social workers and/or other allied mental health professionals are frustrated more with system-related than client-related issues (Acker, 2004;Mason et al, 2004). In light of this research, our current findings suggest that although frustrations with the mental health system may dominate social workers' melee, clientrelated frustrations.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…Furthermore, this lack of influence could not be attributed to an over-representation of private practitioners in our sample. These findings are somewhat surprising given that previous research, including our earlier descriptive analyses (Newhill & Korr, 2004), indicated that modern-day social workers and/or other allied mental health professionals are frustrated more with system-related than client-related issues (Acker, 2004;Mason et al, 2004). In light of this research, our current findings suggest that although frustrations with the mental health system may dominate social workers' melee, clientrelated frustrations.…”
Section: Discussioncontrasting
confidence: 77%
“…Only a brief overview of the methods relevant to this study is presented, as further elaboration on the methodology used in this study is available elsewhere (Newhill, 2003;Newhill & Korr, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Une recherche (Morin, Dorvil et Grenier, 2003) quant àl'univers des maisons de chambre a toutefois dé-montré que celui-ci n'est pas homogène d'un endroit à l'autre mais il est manifeste toutefois que la sécurité l'emporte sur l'autonomie défi-nie par les propriétaires. Une recherche (Newill et Korr, 2004) Plus globalement le zonage, un mécanisme de division des sols et de ségrégation des populations, a joué un rôle majeur dans la reconfiguration des services d'hébergement et dans la reproduction de rapports sociaux fondés sur une distance vis-à-vis de la folie. Le zonage, comme technique de contrôle du territoire, est ainsi devenu l'instrument privilégié d'exclusion des populations marginalisées, aux États-Unis comme au Canada.…”
Section: Revue De Littérature Sur Le Logementunclassified